Kajian Humor Berbahasa Bali Perspektif Taksu North Bali dalam Video "Kawin Campur" - Cahyanti, Ni Kadek Astri (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
Humour is one of the pragmatic studies deadling with the attitude that tends to be done to arouse feelings of joy and trigger laughter. This study aims to reveal Balinese humor from the perspective of Taksu North Bali in the Kawin Campur video. The data source in this study uses primary data sources obtained from Taksu North Bali's YouTube. There are three stages of data collection, namely the first data collection stage using the listening method while repeated viewing technique on Taksu North Bali's YouTube. Second, using the note-taking technique to avoid any missing data. The last stage is the translation technique which aims to translate the Balinese dialogue into Bahasa Indonesia. At the analysis stage, the qualitative data collection is processed by using qualitative methods and qualitative descriptive techniques in which describing the facts, then analyzed using humor studies to determine the humor contained in the Kawin Campur video on the Taksu North Bali YouTube channel. The form of humour presented in the mixed marriage video is understanding, allusion, definition, definite answer, and misunderstanding. Humour presented by the account Youtube Taksu North Bali is not only a means of entertainment, but in the videos also includes moral messages for the audience